Mechanism and Application of Reverse Austenitic Transformation in Medium Mn Steels: A Systematic Review. Issue 10 (3rd October 2022) - Guo, Qinyi; Hu, Bin; Luo, Haiwen
Abstract : To meet the requirement of fuel efficiency and CO2 emission, tremendous efforts have been made in the last decade to improve the mechanical properties of medium Mn steels. In article 2200257, Guo, Hu, and Luo focus on the mechanism of the reverse austenitic transformation kinetics and several processing strategies that utilize these mechanisms for improving mechanical performance.